Strategi Guru Akidah Akhlak Dalam Meningkatkan Karakter Disiplin Siswa - Asropi Asropi; Hidayat Hidayat; Risnita Risnita (Center for Religious Studies and Social Empowerment Foundation, 2022)
This study aims to determine the Teacher Akidah Akhlak Strategy in improving the disciplinary character of students at MTs Al-Hidayatul Islamiyah Tanjung Jabung Barat. This type of research is qualitative research, while all the primary data needed in this study were obtained through research instruments in the form of observation, interviews and documentation, using data analysis techniques, namely data reduction, data presentation and drawing conclusions. The results of this study indicate that the description of student discipline at Mts Al-Hidaytul Islamiyah Tanjung Jabung Barat, namely the discipline of study time according to the subject roster schedule that applies every semester, and appearance in accordance with school rules, students are emphasized to always obey the rules, and every student is obliged to attend midday prayers in congregation. Factors that hinder teachers in improving student discipline are the first factor namely the factors of the students themselves, the lack of awareness of students towards school rules and there is an element of compulsion in carrying out disciplinary habits and the condition of students who are not sincere and lazy to participate in learning activities. Penelitian ini bertujuan untuk mengetahui Strategi Guru Akidah Akhlak dalam meningkatkan karakter disiplin siswa di MTs Al-Hidayatul Islamiyah tanjung Jabung Barat. Jenis penelitian ini adalah penelitian kualitatif, adapun seluruh data primer yang diperlukan dalam penelitian ini diperoleh melalui instrument penelitian berupa observasi, wawancara dan dokumentasi, dengan menggunakan teknik analisis data yaitu reduksi data, penyajian data dan menarik kesimpulan. Hasil penelitian ini menunjukkan bahwa Gambaran kedisiplinan siswa di Mts Al-Hidaytul Islamiyah Tanjung Jabung Barat yakni disiplin waktu belajar sesuai dengan jadwal roster mata pelajaran yang berlaku pada setiap semester, serta berpenampilan sesuai dengan tata tertib sekolah, siswa ditekankan agar selalu taat terhadap tata tertib, dan setiap siswa wajib mengikuti sholat dzuhur secara berjamaah. Faktor yang menghambat guru dalam meningkatkan kedisiplinan siswa yaitu faktor pertama yakni faktor dari siswa itu sendiri, kurangnya kesadaran siswa terhadap tata tertib di sekolah serta ada unsur keterpaksaan dalam menjalankan pembiasaan kedisiplinan dan kondisi siswa yang tidak ikhlas dan malas mengikuti kegiatan belajar.